Dynamic Succession of Ecosystem Services in Rural Areas: Trade-offs, Synergies, and Driving Mechanisms - Liu, Xinyi (International Journal of Natural Resources and Environmental Studies, 2026)
The intensification of urbanization has exacerbated the conflict between the stability of rural ecosystems and economic development. Understanding the dynamic succession of ecosystem services (ESs) in rural areas is essential for achieving regional ecological sustainability. This study assessed seven ESs in the rural areas of Hangzhou from 2000 to 2020, analyzing their spatiotemporal evolution characteristics, dynamic changes in trade-offs/synergies, and driving mechanisms. The results showed that: (1) ESs exhibited a spatial distribution pattern characterized by “high in the southwest and low in the northeast.” Soil conservation and cultural services showed an overall upward trend, water yield and water purification first increased and then declined, while carbon storage, habitat quality, and food production declined continuously. (2) Among the 21 ES pairs, eight exhibited significant correlations, with notable changes observed in pairs related to food production, cultural services, and habitat quality. (3) Among the prominent trade-off/synergy pairs, socio-economic factors were identified as the dominant drivers of changes in ES trade-offs/synergies in Hangzhou‘s rural areas.